Effects of riverbank erosion on the stability of surrounding infrastructure: A case study of the Nolhaga wastewater treatment plant - Theodorsson, Emil (My University, 2024)
The impacts of climate change, such as more frequent and severe rainfall and longer periods of drought, may heighten the likelihood and regularity of erosion along riverbanks. This could result in negative outcomes for both ecosystems and human activities in the vicinity. Most studies that analyse the effects of bank erosion do not account for the influence of soil properties such as anisotropy or creep. They also rarely investigate how surrounding structures are affected by the erosion process. This thesis aims to use the data collected from the Nolhaga wastewater treatment plant in Alingsås as a case study to assess these aspects. Regarding soil constitutive models, a comparison between the use of simple to more complex models have been considered in this thesis. The constitutive models considered include Mohr-Coulomb, Soft Soil Creep, and Creep-SCLAY1S. The Nolhaga test site is modelled in PLAXIS 2D finite element code as several 2D plane strain sections, using site investigation data as a source to model the geometry and soil properties. A total of five sections are modeled, the locations of which are based on a previously performed stability analysis. The assumed bank erosion rate and patterns are simplified to be equal across all five modeled sections, as well as evenly distributed over the entire riverbed that is below water. The majority of the loads considered in the sections are based on previous stability analyses. However, some have updated values from more recent load estimations. The results show that Creep-SCLAY1S generally predicts the highest vertical and horizontal displacements in the modeled sections, with Soft Soil Creep predicting the second highest vertical displacements, and Mohr-Coulomb predicting the second highest horizontal ones. The calculated safety factors of the riverbanks decrease with time as a direct result of modelling erosion, with some areas dropping below a safety factor of 1 within the studied time frame, indicating a risk of failure. Based on a displacement comparison with a non-erosion scenario, bank erosion has a large impact on predicted horizontal displacements, while having significantly less impact on the vertical ones. Based on a performed pipe tolerance assessment, the treatment plant pipelines are deemed to be at risk of suffering damage by the calculated displacements, with the influence of erosion on these risks being negligible. However, due to lack of relevant site data, there are large uncertainties related to these results. Thus, further investigations are recommended to gather more information and decrease these uncertainties.
Keywords: groundwater modelling